INFLUENCE PHYSICAL WORK ENVIRONMENT AND NON-PHYSICAL IN THE EMPLOYEE PERFORMANCE OF KPPN BANDUNG I - Eldaa Cintia Siagian (Jurnal Sosioteknologi, 2016)
Abstract The enhancement of employee performance is required in order to achieve the goal of the company. There are plenty of things affect the performance of employee, one of them is the work environment, which is generally divided into two category namely the physical work environment and non-physical work environment. Therefore the purpose by doing this research is to see the influence between physical work and non-physical work environment toward employee performance in KPPN Bandung I. Data analysis technique used in this research are descriptive analysis and multiple linear regression analysis method that previously have been tested with the classical assumption of normality test, multicollinearity test, heteroscedasticity test, F test, t-test, the coefficient of determination (R2) and data processing used by SPSS software version 16.0.Based on research by using 45 respondents, it could be be seen that the result of multiple linear regression showed partialy physical work environment such as work equipment, ventilation, noise, lighting, and layout have a significant influence on employee performance amounted to 44.9%. Furthermore, non-physical work environment such as superior and subordinate work relationship or among fellow employees also have a significant influence on employee performance amounted to 42.8%. The simultaneous test result showed the physical and non-physical work environment as well have a significant influence on employee performance amounted to 72.1%. Therefore the result of this study showed that either partially or simultaneously, physical work and non-physical work environment have a significant impact on the performance of employees at Bandung KPPN I. Keywords : Physical Work Environment, Non-Physical Work Environment, Employee Performance.